A transesterification-based epoxy vitrimer synthesis enabled high crack self-healing efficiency to fibrous composites. (November 2022) - Wu, Pan; Liu, Ling; Wu, Zhanjun
Graphical abstract: Highlights: A dicarboxylic acid, a general epoxy resin and a primary amine (and CNTs) are used to synthetize a novel epoxy vitrimer with improved transesterification rate. The epoxy vitrimer has good self-healing efficiency to their own cracks as well as to the delamination crack of CFRP with epoxy vitrimer matrix. The obtained CFRP show effective self-healing ability to manufacturing defects and low-temperature induced microcracks. Abstract: Adipic acid was grafted onto a general epoxy resin and then crosslinked with a primary amine to synthesize a novel remenable epoxy vitrimer (EPV). Also, carbon nanotubes were added into EPV to obtain reinforced EPVC. Results reveal that EPV and EPVC show good self-healing efficiencies to their respective cracks, i.e. 74–77 % to fracture toughness and 62–67 % to tensile strength. But EPVC shows higher toughness and strength, respectively increased by 80 % and 3.2 % when compared with EPV. Also, the obtained fibrous composites are resistant to low temperature and the increased crack density is only 0.02 % after soaking in liquid nitrogen for 20 days, which can be completely healed by thermal activation. Moreover, EPV and EPVC-based laminates show a self-healing efficiency greater than 100 % to interlaminar toughness and strength after two loading-healing cycles. The EPVC laminate also has higher initial mechanical properties. Thus, the synthesized EPV/EPVC is potential in preparing self-healing structural composites.